Predicting complexity in transurethral resection of bladder tumours: external validation and modification of the bladder complexity score - Grüne, Britta; Kowalewski, Karl-Friedrich; Weiß, Christel; Neuberger, Manuel; Nientiedt, Malin; Wenk, Maren; Hartung, Friedrich; Kriegmair, Maximilian; Waldbillig, Frank (Urologia internationalis, 2023)
Introduction: First external validation of the Bladder Complexity Score (BCS) for predicting complex transurethral resection of bladder tumours (TURBT). Methods: For BCS calculation, TURBTs performed at our institution between January 2018 and December 2019 were reviewed for the presence of preoperative characteristics listed in the Bladder Complexity Checklist (BCC). Receiver operating characteristics (ROC) analysis was used for BCS validation. To establish a modified BCS (mBCS) with maximum area under the curve (AUC), multivariable logistic regression (MLR) analysis was performed with all BCC-characteristics for different definitions of complex TURBT. Results: 723 TURBTs were included in statistical analyses. Cohort’s mean BCS was 11.2 ± 2.4 points (range: 5.5-22 points). In ROC analysis, BCS could not predict complex TURBT (AUC 0.573 [95% CI: 0.517-0.628]). MLR identified tumour size (OR 2.662, p < 0.001), and tumour number > 10 (OR 6.390, p = 0.032) as sole predictors for the modified endpoint of complex TURBT defined as a procedure meeting > 1 criterion: incomplete resection, surgery > 1 h, intraoperative complication, postoperative complications Clavien-Dindo ≥ III. mBCS increased the prediction to an AUC of 0.770 (95% CI: 0.667-0.874). Conclusion: In this first external validation, BCS remained an insufficient predictor of complex TURBT. mBCS requires reduced parameters, is more predictive and easier to apply in clinical practice.
Online veröffentlicht: 13. Juni 2023
Gesehen am 20.08.2024